Investment Activities of the Polish YMCA in the Interwar Period - Potrzuski Kamil; Włodarczyk Arkadiusz (Sciendo, 2022)
Young Men's Christian Association (YMCA) appeared in Poland in 1918. Three years later, the American branch of the organization ceased its activity in this country. In its place the Christian Young People Association 'Polska YMCA' (The Polish YMCA) was established. This organization, although maintained contact with the centers of organizations in other countries, remained fully independent. The Polish YMCA was most active in large cities and centers of particular symbolic and economic importance for the Second Republic of Poland - Warsaw, Cracow, Łódź and Gdynia. The Polish YMCA was one of the most active and efficient social organizations dealing with physical education and sport in interwar Poland. It gained considerable popularity and was one of the most important institutions offering extracurricular activities for young people. One of the reasons for its success was its excellent material base. The Polish YMCA successfully built three representative buildings in the center of Cracow, Warsaw and Łódź in the interwar period. Their construction was partially financed by American funds. There were sports equipment, rare in interwar Poland, such as indoor swimming pools, sports halls and indoor tennis courts located in there. The Polish YMCA also developed the infrastructure of summer camps.